Portugal : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1999)
This paper reviews economic developments in Portugal-Macau during 1997-99. It highlights the way in which Macau's economic development evolved over the years. The paper discusses developments in prices, wages, and employment, and sheds light on how the product and labor markets adjusted to external shocks-in particular to the Asian crisis as well as the increased competition faced by the economy in recent years (1997-99). The paper also reviews the budgetary process and budgetary developments and highlights structural problems that are inherent in the fiscal system.